Diaspora and home: contextualizing the idea of home in Australian contemporary art as visualised by selected Iranian artists - Rakhsha, Layli (Curtin University, 2018)
This practice-led research project investigates the impact of displacement on the idea of home in the new place. By focusing on some Iranian migrants who practice art in Australia and analysing their selected works, this project aims to discuss how memories from the past and imaginations can influence on the idea of home in the new place, and how home can be visualised based on experiences of migration and displacement. Considering the emotional impact of displacement on the idea of home, and Iranian collaborators’ responses to the definitions of home and homeland, as well as producing artworks, this studio based research project explores home can be defined within personal experiences, social and cultural relationships and attachments to a particular place.